Ultrafast quasiparticle dynamics in Tl2Ba2CuO6+δ - Smith, D; Gay, P; Wang, D; Wang, J; Ren, Z; Ryan, J (Elsevier, 2000)

(untitled)
We present measurements of the ultrafast time-resolved reflectance of optimally doped Tl2Ba2CuO6+δ. The superconducting state response is interpreted in terms of pair formation from non-equilibrium quasiparticles in the nodes of a d-wave superconducting gap.